Ki67 as a prognostic marker in uterine leiomyosarcoma: A quantitative systematic review. (November 2021) - Travaglino, Antonio; Raffone, Antonio; Catena, Ursula; De Luca, Marcello; Toscano, Paolo; Del Prete, Ester; Vecchione, Maria Luisa; Lionetti, Ruggero; Zullo, Fulvio; Insabato, Luigi
Abstract: Ki67 labeling index (LI) has been proposed as a prognostic factor in uterine leiomyosarcoma (uLMS), although the evidence in this field is still unclear. We aimed to assess the prognostic value of ki67 LI in uLMS. A systematic review was performed by searching electronic databases from their inception to August 2020 for all studies assessing the prognostic value of ki67 LI in uLMS. Ki67 LI was assessed to the nearest 10% to define the most prognostically accurate threshold. Cox regression survival analysis with calculation of hazard ratio (HR) of death was performed; a p-value < 0.05 was considered significant. Ten studies were included in the qualitative review, out of which 6 were suitable for quantitative review. The absolute risk of death was 0.29 for a ki67 LI < 10%, remained stable at 0.49 in the 10%-39% LI range and increased to 0.65 for a LI ≥ 40%. On univariate analysis, both 10% and 40% thresholds were significantly associated with the hazard of death, with HRs of 3.349 (p = 0.007) and 3.172 (p = 0.001), respectively. On multivariate analysis, only the 10% threshold was significantly associated with the hazard of death (HR = 2.712; p = 0.028). In conclusion, a Ki67 LI ≥ 10% is a significant prognostic factor in uLMS.